2023
DOI: 10.3390/healthcare11060875
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of TeleHealth and Digital Healthcare: Where Are We?

Abstract: Due to the development of the technological innovation of devices, availability of increasingly performing networks, improvement of the digitization processes, and the push to greater diffusion determined by the COVID-19 pandemic, Digital Healthcare (DH), also referred to as Digital Health [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…These kinds of devices have enormous potential to ensure better care and an improved sense of security and quality of life for older adults [3]. Indeed, in the last decade, digital healthcare technologies have rapidly grown in diagnostics, therapy, assistance, epidemiology, and other sectors [38], but, as demonstrated by this study, when such tools match the older population market, different barriers must be considered. In this study, we focused on usability and acceptance, and we also mentioned the lack of knowledge on how to use and benefit from technology [4,5].…”
Section: Discussionmentioning
confidence: 95%
“…These kinds of devices have enormous potential to ensure better care and an improved sense of security and quality of life for older adults [3]. Indeed, in the last decade, digital healthcare technologies have rapidly grown in diagnostics, therapy, assistance, epidemiology, and other sectors [38], but, as demonstrated by this study, when such tools match the older population market, different barriers must be considered. In this study, we focused on usability and acceptance, and we also mentioned the lack of knowledge on how to use and benefit from technology [4,5].…”
Section: Discussionmentioning
confidence: 95%
“…However, there has been considerable variation in the delivery mode of available digital solutions, namely in the involvement of humans as coaches or health care providers. A common feature across most digital health programs is the inclusion of human coaching or care provision delivered via telephone calls, SMS text messaging, or email [17]. Moreover, a recent review of the literature indicated that very few (4/31, 13%) cardiovascular health-related digital health interventions are fully automated, requiring no specific personnel [11].…”
Section: Digital Health Solutions For Cvd Preventionmentioning
confidence: 99%
“…4 With the rapid development of new technologies in the past decade, such as ubiquitous smart devices and advances in artificial intelligence, it is essential to review the current evidence of how these tools affect caregivers. Digital health refers to “the use of information and communications technologies in medicine and other health professions to manage illnesses and health risks and to promote wellness.” 5 It compasses mobile health, telehealth, wearable devices, health information system, and telemedicine. 5 So far, several existing systematic literature reviews have mainly focused on caregivers of adults or older adults with dementia, cancer, or late-life diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Digital health refers to “the use of information and communications technologies in medicine and other health professions to manage illnesses and health risks and to promote wellness.” 5 It compasses mobile health, telehealth, wearable devices, health information system, and telemedicine. 5 So far, several existing systematic literature reviews have mainly focused on caregivers of adults or older adults with dementia, cancer, or late-life diseases. 5 , 9 Two systematic reviews focused only on web-based interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation